Al-Raisuni's Maqasid al-Shari’ah as an Audit Framework for Indonesian Green Sukuk - Hasby Cholili; Aep Saepullah; Mualimin Mochammad Sahid (Mauriduna : Journal of Islamic Studies, 2026)
This study evaluated Indonesia's Sovereign Green Sukuk through Ahmad Al-Raisuni's tripartite Maqāṣid al-Sharī'ah framework, examining whether the instrument achieved substantive environmental objectives or merely fulfilled administrative compliance. Employing normative-juridical documentary analysis, the research examined three primary source categories: POJK No. 18/2023 governing issuance requirements; Al-Raisuni's foundational Arabic texts; and the Ministry of Finance's Green Sukuk Allocation and Impact Reports (2018–2022). Content analysis with deductive reasoning was applied to assess operational effectiveness, governance architecture, and reporting mechanisms relevant to greenwashing mitigation. The findings indicated that Indonesia's framework exhibited stronger impact-measurement alignment than market-centric models, as evidenced by a government-reported cumulative emission reduction of 10.6 million tonnes of CO₂ across 2018–2022, through infrastructure projects in remote 3T regions including flood control systems and solar PV installations at disaster monitoring posts. The study contributed a hierarchical audit framework that operationalised Al-Raisuni's Partial, Special, and General Maqāṣid Objectives as evaluative checkpoints for assessing use-of-proceeds governance and greenwashing resilience.